2021
DOI: 10.21203/rs.3.rs-52520/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CT radiomics for predicting PD-L1 expression on tumor cells in gastric cancer

Abstract: Purpose To explore CT radiomics for predicting programmed cell death ligand 1 on tumor cells (PD-L1) status in gastric cancer (GC).Methods From March 2019 to July 2020, 358 patients identified with GC who underwent surgery at our hospital were enrolled in this study retrospectively. All patients were divided into primary (n=239) and validation (n=119) cohorts based on the time of surgery at a ratio of 3:1. Radiomic features were extracted from regions of interest manually drawn on venous CT images. Besides, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A significant achievement in radiogenomics is developing a fully automated system combined with a radiological workflow, shown in Figure 9 [ 113 ]. This reduces the overall time involved in performing repetitive and tedious tasks while improving efficiency and productivity [ 114 , 115 ]. Another advantage is the real-time monitoring of treatment by simultaneously comparing several images from the database [ 113 , 114 ].…”
Section: What Have We Achieved So Far In Radiogenomics?mentioning
confidence: 99%
“…A significant achievement in radiogenomics is developing a fully automated system combined with a radiological workflow, shown in Figure 9 [ 113 ]. This reduces the overall time involved in performing repetitive and tedious tasks while improving efficiency and productivity [ 114 , 115 ]. Another advantage is the real-time monitoring of treatment by simultaneously comparing several images from the database [ 113 , 114 ].…”
Section: What Have We Achieved So Far In Radiogenomics?mentioning
confidence: 99%
“…The development of a completely automated system paired with a radiological workflow, such as the one represented in Figure 8 [ 144 ], is a notable breakthrough in the field of radiogenomics. This results in a reduction in the total amount of time spent performing tasks that are repetitive and laborious, while simultaneously boosting both efficiency and productivity [ 145 , 146 ]. Another advantage is that the treatment can be monitored in real-time by comparing many photos from the database at the same time [ 144 , 146 ].…”
Section: An Overview Of Artificial Intelligence Applications In Healt...mentioning
confidence: 99%
“…This results in a reduction in the total amount of time spent performing tasks that are repetitive and laborious, while simultaneously boosting both efficiency and productivity [ 145 , 146 ]. Another advantage is that the treatment can be monitored in real-time by comparing many photos from the database at the same time [ 144 , 146 ].…”
Section: An Overview Of Artificial Intelligence Applications In Healt...mentioning
confidence: 99%
“…In other words, textural features with high association with the PD-L1 expression level were those extracted from the CT portion. Recent studies have revealed that CT texture parameters could be useful for predicting PD-L1 expression in several cancers (35,36). Jiang et al also reported that textural features extracted from CT performed better than those of PET in assessing the expression status of PD-L1 in NSCLC (15).…”
Section: Representative Positron Emission Tomography/computed Tomogra...mentioning
confidence: 99%